Religion Acculturation With Merariq Lombok Traditions, A Study Of The Sorong Serah Aji Krama Procession Symbolic Meaning From A Cultural Communication Perspective - Ikhsan, Ikhsan (Riwayat: Educational Journal of History and Humanities, 2024)
The blend of cultural and religious values in theMerariq tradition of the Sasak people is closely related to the perspective of artistic communication. Communication and culture have a very close relationship, where one of the main functions of communication is to disseminate culture. The cultural communication process in question encompasses all stages in the Merariq tradition. This research uses qualitative methods with a descriptive qualitative approach and applies Herbert Blumer's symbolic interactionism as the theoretical framework. The study results show that integrating religious and cultural values in the Merariq tradition produces a harmonious blend. This acculturation has elevated the status of both values to a higher level.